Design of steel frames equipped with BRBs in the framework of Eurocode 8. (October 2015) - Bosco, M.; Marino, E.M.; Rossi, P.P.
Abstract: Buckling restrained braces (BRBs) have been investigated extensively by means of experimental tests and their large ductility has been pointed out by many studies. Nevertheless, Eurocode 8 (EC8) does not provide any rules for design of steel frames with BRBs. For this reason, a design procedure for steel frames equipped with BRBs is proposed in this paper. The proposed design procedure is obtained by modifying the rules stipulated in EC8 for steel chevron braced frames. As a consequence, the obtained design procedure is consistent with the framework of EC8. BRBs are designed in terms of ductility and strength based on two parameters: the design storey drift Δ u d, i.e. the maximum accepted storey drift demand for earthquakes with a given probability of occurrence, and the behaviour factor q, which is a seismic force reduction factor correlated with the expected ductility of the structure. Beams and columns are designed according to capacity design principles derived from those given in EC8 with reference to steel chevron braced frames. The design procedure is applied to a set of multi-storey frames with BRBs assuming different values of Δ u d and q . Their seismic response is evaluated by nonlinear dynamic analysis for two seismic excitation levels. The BRBs are modelled by a refined numerical model calibrated on the basis of a wide database of experimental data. For each value of Δ u d, the highest values of q leading to seismic response that does not exceed the Significant Damage and Near Collapse limit states are determined. Then, the suggested behaviour factor is given as a function of the design storey drift. Highlights: The paper proposes a design procedure for steel frames with BRBs. The proposed procedure is consistent with Eurocode 8. The design method takes into account the available ductility of the adopted BRBs. The behaviour factor q for the determination of the seismic design force is provided. Numerical model of BRBs is calibrated based on of a large set of experimental data.